Impact of malignancy on outcomes in European patients with atrial fibrillation: A report from the ESC-EHRA EURObservational research programme in atrial fibrillation general long-term registry - Malavasi, Vincenzo L; Vitolo, Marco; Proietti, Marco; Diemberger, Igor; Fauchier, Laurent; Marin, Francisco; Nabauer, Michael; Potpara, Tatjana S; Dan, Gheorghe-Andrei; Kalarus, Zbigniew; Tavazzi, Luigi; Maggioni, Aldo Pietro; et al. (Wiley, 2022)
The management of patients with atrial fibrillation (AF) and malignancy is challenging given the paucity of evidence supporting their appropriate clinical management.
Keywords: atrial fibrillation; malignancy; clinical management